In the Digital Spheres: Navigating Artificial Intelligence in Teaching - Dela Cruz, John Michael M.; Sales, Angelie G.; Ularte, Marrie Vic Barrios; Pasco, Eric P.; Ortiz Jr., Oliver E. (Future Science / FSH-PH Publications, 2025)
Artificial Intelligence is one of the most advanced technological tool which was developed to proceed convenient and fastest gen-eration of ideas and concepts. This study described and examined the use and effectiveness of artificial intelligence in the traditional teaching landscape in the study. It utilized descriptive correlation-al research design where researcher-made questionnaire was used as the main instrument of the study. It was participated by 500 public secondary teachers in the Philippines. Findings showed that Artificial Intelligence as perceived by teachers was useful and directly beneficial to facilitate effective and retentive instruction, effectively provides relevant and highly diversified instructional methods and strategies which teachers can use in order to cater the individual needs and interests of learners and provides enor-mous amount of assessment styles, procedures and methods that objectively assess learners’ academic performances. Also, AI is perceived by teachers to be an effective tool in providing effective learning acquisition process as AI provides accurate data which are timely and relevant, provides instructional styles and methods which are practical and highly engaging and institute authentic assessment s that reflect real-world activities thereby promoting effective transfer of learning. Apparently, as the effectiveness of AI in instruction increases, learners’ learning acquisition also in-creases. AI as digital platform help increase instructional compe-tence of teachers through provision of accurate and reliable infor-mation or data gathered which can be potentially used during the teaching and learning process.